Peranan Alumni Pondok Pesantren Syekh Muhammad Dahlan Aek Hayuara Sibuhuan dalam Mengembangkan Pendidikan di Wilayah Kecamatan Barumun - Amar Makruf Rangkuti; Zainal Efendi Hasibuan (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this research is to describe the extent of the role of the alumni of the Sheikh Muhammad Dahlan Aek Hayuara Sibuhuan Islamic Boarding School in advancing education in the Barumun District Area. The Islamic Boarding School, which is the oldest in Padang Lawas district, has graduated many of the best alumni, ranging from great Ulama, Think Figures, ASN, TNI/POLRI, Islamic Boarding School Leaders, Lecturers in Higher Education, and Teachers in various formal and non-formal Educational Institutions. The Islamic boarding school which was established in 1938 was founded by Sheikh Muhammad Dahlan Hasibuan. The role of alumni in developing education has a significant impact and covers various aspects that are essential for the progress of educational institutions. Alumni, as a product of the education system, have experience, knowledge, and resources that can be utilized to support the development of education. They can contribute through improving the quality of education by acting as mentors, providing advice based on professional experience, and sharing information on relevant industry needs. In addition, financial support from alumni through donations, scholarships, and fundraising can help educational institutions in providing better facilities and innovative programs.